Public sphere and global governance - Michael Zürn (Philosophy & Social Criticism, 2024)
This paper is about the effects of the absence and the possibility of the emergence of a normatively meaningful political public sphere. The effects of the lack of a global public sphere are far-reaching. Namely, the current crisis of global governance and the global political system can be traced back to the absence of a normatively meaningful public sphere that can mediate between global society and the authoritative institutions of global governance. At the same time, I argue that the absence of the public sphere is not primarily due to the population's attitudes trapped in national horizons but must be primarily attributed to the deficient institutional structure of the global political system.
Keywords: 320; authority; deliberation; global governance; global society; legitimacy; international institutions; public sphere